1999
DOI: 10.1677/jme.0.0230299
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism for the melatonin inhibition of testosterone secretion by rat Leydig cells: reduction of GnRH-induced increase in cytosolic Ca2+

Abstract: The site of inhibition, by melatonin, of GnRHdependent testosterone secretion was investigated in adult rat Leydig cells cultured in vitro. The various effects downstream of the binding of GnRH to its own receptor were isolated and mimicked by specific drugs. Testosterone secretion was then evaluated after 3 h stimulation with GnRH, thapsigargin (1 µM), phorbol-12-myristate-13-acetate (100 nM), arachidonic acid (20 µM), and ionomycin (1 µM) in the presence or absence of melatonin (215 nM). The effect of melato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…Since we observed no changes in DHAS production, minor compensatory adjustments at steps in the synthesis of DHAS involving Steroidogenic Acute Regulatory protein (StAR), or the enzymes cholesterol side‐chain cleavage cytochrome P450 (P450scc) and cytochrome P450 17‐hydroxylase (P450c17) may have occurred. This possibility needs to be investigated, given that melatonin decreases human chorionic gonadotropin (HCG)‐stimulated mitochondrial StAR in a line of Leydig cells (Wu et al 2001) and results in accumulation of 17‐OH progesterone in gonadotropin releasing hormone (GnRH)‐stimulated rat Leydig cell cultures (Valenti et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Since we observed no changes in DHAS production, minor compensatory adjustments at steps in the synthesis of DHAS involving Steroidogenic Acute Regulatory protein (StAR), or the enzymes cholesterol side‐chain cleavage cytochrome P450 (P450scc) and cytochrome P450 17‐hydroxylase (P450c17) may have occurred. This possibility needs to be investigated, given that melatonin decreases human chorionic gonadotropin (HCG)‐stimulated mitochondrial StAR in a line of Leydig cells (Wu et al 2001) and results in accumulation of 17‐OH progesterone in gonadotropin releasing hormone (GnRH)‐stimulated rat Leydig cell cultures (Valenti et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies indicate that melatonin can modify the firing frequency of the hypothalamic gonadotropin-releasing hormone pulse generator, thereby affecting the release of gonadotropins (luteinizing hormone and follicle-stimulating hormone) from the pituitary (10-13) and stimulating testicular testosterone or ovarian estrogen production and release (14,15). Animal studies have also shown that melatonin can inhibit luteinizing hormone-induced testosterone production in rats (16)(17)(18), inhibits prolactin cell activity in male and female hamsters (19), and suppresses several aspects of reproductive physiology in male hamsters (20). Human studies indicate that decreased concentrations of circulating melatonin (such as those brought about by circadian disruption) can result in increased release of the gonadotropins luteinizing hormone and follicle-stimulating hormone from the pituitary and estrogen release by the ovaries (21)(22)(23)(24)(25).…”
Section: Cancer Epidemiol Biomarkers Prev 2008;17(12) December 2008mentioning
confidence: 99%
“…Moreover, Valenti et al, (1999) concluded that MEL reduces gonadotropin releasing hormone(GnRH)-induced testosterone secretion by decreasing cytoplasmic calcium concentration, through impairment of the GnRH-dependent release of calcium from intracellular stores and blocking 17-20 desmolase enzymatic activity, an effect that occurs irrespective of changes in calcium concentration.…”
Section: Discussionmentioning
confidence: 99%